Design considerations for the design of an advanced VR interface for knowledge management and its relevance to CAD - Mohamed Eshaq, A (2003)
This paper introduces knowledge management as a key in establishing both valuation and value creation capabilities in the enterprise where dissemination of knowledge and effective sharing of information through collaboration spur creativity and stimulate business practices. The paper draws an original approach for the design and development of a universal information/knowledge visualisation tool, elucidates the mechanics that enable the working prototype and most important it elaborates on the concepts that have led to the adopted architecture. Finally it presents the next step in the system's development cycle outlining its architecture and direction. (C) 2003 Elsevier B.V. All rights reserved.